The sTREM2 Concentrations in the Blood: A Marker of Neurodegeneration? - Ferri, Evelyn; Rossi, Paolo Dionigi; Geraci, Annalisa; Ciccone, Simona; Cesari, Matteo; Arosio, Beatrice (Frontiers in Molecular Biosciences, 2021)
Microglia performs a variety of functions during brain development designed to maintain brain homeostasis. Triggering receptor expressed on myeloid cells 2 (TREM2) is expressed in microglial cells modulating phagocytosis, cytokine production, cell proliferation, and cell survival. Interestingly, the levels of soluble TREM2 (the secreted ectodomain of TREM2, sTREM2) were higher in cerebrospinal fluid (CSF) from Alzheimer's disease (AD) patients than subjects without cognitive decline. It is noteworthy that, while CSF sTREM2 levels have been extensively studied, few studies have investigated sTREM2 in blood producing conflicting results. We aimed to investigate the levels of sTREM2 in CSF and blood from a cohort of well-characterized AD comparing the results to those obtained in patients suffering from idiopathic normal pressure hydrocephalus (iNPH), a potentially reversible cognitive impairment. Our findings underlined a significantly lower plasma sTREM2 concentration in AD patients compared to iNPH subjects [39.1 ng/mL (standard deviation (SD), 15.0) and 47.2 ng/mL (SD, 19.5), respectively; p = 0.01], whereas no difference was revealed between the two groups in the CSF sTREM2 levels. The adjusted regression analyses evidenced in AD patients an association between plasma and CSF sTREM2 levels [B = 0.411; 95% confidence interval (CI), 0.137–0.685, p = 0.004], as well as β-amyloid concentrations (B = 0.035; 95% CI, 0.007–0.063, p = 0.01) and an association between CSF sTREM2 and phospho-Tau concentrations (B = 0.248; 95% CI, 0.053–0.443; p = 0.01). No significant relation was found in iNPH patients. In conclusion, these differences in sTREM2 profiles between AD and iNPH reinforce the notion that this receptor has a role in neurodegeneration.